2022
DOI: 10.3390/ijms23105448
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Blockade via PD-L1 Potentiates More CD28-Based than 4-1BB-Based Anti-Carbonic Anhydrase IX Chimeric Antigen Receptor T Cells

Abstract: The complete regression of clear cell renal cell carcinoma (ccRCC) obtained pre-clinically with anti-carbonic anhydrase IX (CAIX) G36 chimeric antigen receptor (CAR) T cells in doses equivalent to ≅108 CAR T cells/kg renewed the potential of this target to treat ccRCC and other tumors in hypoxia. The immune checkpoint blockade (ICB) brought durable clinical responses in advanced ccRCC and other tumors. Here, we tested CD8α/4-1BB compared to CD28-based anti-CAIX CAR peripheral blood mononuclear cells (PBMCs) re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…To enhance the antitumor activity of CAR T cells against CD19 positive B-ALL and Her2 positive breast cancers, we inserted CD19.BBz, CD19.BBz.PD-L1, Her2.BBz, and Her2.BBz.PD-L1 CARs into the multi-cloning site of pCDH-EF1α-MCS-CMV-copGFP vector ( Figure 1 A). We chose the 4-1BB signaling fragment due to its greater persistence of CAR T cells in vivo [ 7 , 20 ]. The IRES (internal ribosome entry site) allows the translation of scFv PD-L1 antibody.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To enhance the antitumor activity of CAR T cells against CD19 positive B-ALL and Her2 positive breast cancers, we inserted CD19.BBz, CD19.BBz.PD-L1, Her2.BBz, and Her2.BBz.PD-L1 CARs into the multi-cloning site of pCDH-EF1α-MCS-CMV-copGFP vector ( Figure 1 A). We chose the 4-1BB signaling fragment due to its greater persistence of CAR T cells in vivo [ 7 , 20 ]. The IRES (internal ribosome entry site) allows the translation of scFv PD-L1 antibody.…”
Section: Resultsmentioning
confidence: 99%
“…A large body of research has revealed that the exhaustion of CAR T cells can be reversed by blocking the PD-1/PD-L1 signaling pathway [ 7 , 8 ]. A combination of CAR T cells with immune checkpoint blocking (ICB) drugs has been used in the treatment of multiple tumors with much improved efficacy [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A relevant number of papers dealing with this enzyme, its inhibitors, activators and involvement in various diseases have been published in 2022 in this journal [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. The first group of contributed materials dealt with the use of this protein for investigations of basic biochemical approaches, such as protein folding [ 7 ], thermodynamic parameters assessment for protein–ligand interactions [ 8 ], bioluminescence resonance energy transfer connected to the binding of the metal ion to apoenzymes [ 9 ], the possibility to evidence chalcogen bonds in the X-ray crystal structures of CA–lig and adduct [ 10 ].…”
Section: State Of the Artmentioning
confidence: 99%